Preservation effect of imeglimin on pancreatic β-cell mass: Noninvasive evaluation using 111In-exendin-4 SPECT/CT imaging and the perspective of mitochondrial involvements - Fauzi, Muhammad; Murakami, Takaaki; Fujimoto, Hiroyuki; Botagarova, Ainur; Sakaki, Kentaro; Kiyobayashi, Sakura; Ogura, Masahito; Inagaki, Nobuya (Frontiers in Endocrinology, 2022)
Progressive loss of β-cell mass (BCM) has a pernicious influence on type 2 diabetes mellitus (T2DM); evaluation of BCM has conventionally required an invasive method that provides only cross-sectional data. However, a noninvasive approach to longitudinal assessment of BCM in living subjects using an indium 111–labeled exendin-4 derivative ([Lys12(111In-BnDTPA-Ahx)]exendin-4) (111In-exendin-4) has been developed recently. Imeglimin is a novel antidiabetic agent that is reported to improve glycemic control and glucose-stimulated insulin secretion (GSIS) via augmentation of mitochondrial function. However, the influence of imeglimin on BCM is not fully understood. We have investigated the effects of imeglimin on BCM in vivo in prediabetic db/db mice using a noninvasive 111In-exendin-4 single-photon emission computed tomography/computed tomography (SPECT/CT) technique. During the 5-week study period, imeglimin treatment attenuated the progression of glucose intolerance, and imeglimin-treated mice retained greater BCM than control, which was consistent with the results of 111In-exendin-4 SPECT/CT scans. Furthermore, immunohistochemical analysis revealed reduced β-cell apoptosis in the imeglimin-treated db/db mice, and also lowered release of cytosolic cytochrome c protein in the β cells. Furthermore, electron microscopy observation and membrane potential measurement revealed improved structural integrity and membrane potential of the mitochondria of imeglimin-treated islets, respectively. These results demonstrate attenuation of progression of BCM loss in prediabetic db/db mice partly via inhibition of mitochondria-mediated apoptosis.